2018
DOI: 10.1113/jp276508
|View full text |Cite
|
Sign up to set email alerts
|

TBX18 overexpression enhances pacemaker function in a rat subsidiary atrial pacemaker model of sick sinus syndrome

Abstract: Key points The sinoatrial node (SAN) is the primary pacemaker of the heart. SAN dysfunction, or ‘sick sinus syndrome’, can cause excessively slow heart rates and pauses, leading to exercise limitation and syncope, currently treated by implantation of an electronic pacemaker.‘Biopacemaking’ utilises gene therapy to restore pacemaker activity by manipulating gene expression. Overexpressing the HCN pacemaker ion channel has been widely used with limited success.We utilised bradycardic rat subsidiary atrial pacema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…TBX18 is attractive target for biopace making as it is important in sinoatrial node development and so has the potential to have a broad effect on cardiac tissue phenotype 26. TBX18 had been associated with the generation of cardiac pacemaker cells and sick sinus syndrome 27 28. TBX18 could have an important role in restoring pacemaker function in human sick sinus syndrome (the most common bradycardia in humans and may increase the risk of sudden death) 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBX18 is attractive target for biopace making as it is important in sinoatrial node development and so has the potential to have a broad effect on cardiac tissue phenotype 26. TBX18 had been associated with the generation of cardiac pacemaker cells and sick sinus syndrome 27 28. TBX18 could have an important role in restoring pacemaker function in human sick sinus syndrome (the most common bradycardia in humans and may increase the risk of sudden death) 28.…”
Section: Discussionmentioning
confidence: 99%
“…TBX18 had been associated with the generation of cardiac pacemaker cells and sick sinus syndrome 27 28. TBX18 could have an important role in restoring pacemaker function in human sick sinus syndrome (the most common bradycardia in humans and may increase the risk of sudden death) 28. KIF6 is ubiquitously expressed in coronary arteries and other vascular tissue and previously related with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…electrophysiological data have shown that iK1 can promote an increase in MdP hyperpolarization, accelerate the four-phase depolarization slope and shorten the aPd, thus increasing the frequency of i(f)-induced automaticity (18). other studies indicated that biological pacemaker activity can also be successfully created by overexpression of T-box18 (TBX18) in vivo (22)(23)(24). The hypothesized mechanisms underlying this phenomenon are as follows: i) TBX18 can convert ventricular myocytes into sinoatrial node-like cells; and ii) TBX18 drives upregulation of Hcn4 or Hcn2, and downregulation of connexin 43, which increases automaticity and the conduction of impulse.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf et al (2013) proposed a computational model of ankyrin-B syndrome SNCs in which alterations of I CaL and NCX as well as I NaK due to ankyrin-B dysfunction increase variability in SN automaticity (Wolf et al, 2013). Choudhury et al (2018) overexpressed NCX1 in bradycardic rat subsidiary atrial pacemaker tissue and found that it did not accelerate the rate of spontaneous depolarizations in contrast to overexpression of TBX18, which increased rate as well as stability and rescued isoproterenol response (Choudhury et al, 2018).…”
Section: Applicationsmentioning
confidence: 99%